The second continuous Jacobi transform - E. Y. Deeba; E. L. Koh (International Journal of Mathematics and Mathematical Sciences)
This paper continues the work started in [1]; a second continuous Jacobi transform is defined for suitable functions f(x). Properties of the transform are studied. In particular, the first continuous Jacobi transform in [1] and the second continuous Jacobi transform are shown to be inverse to each other. The paper concludes with an extension of Campbell's sampling theorem [2].